1984
DOI: 10.1002/jmor.1051820302
|View full text |Cite
|
Sign up to set email alerts
|

Variation and timing of the cranial ossification sequence of the oriental fire‐bellied toad, Bombina orientalis (Amphibia, Discoglossidae)

Abstract: The sequence of appearance of the 17 different skull bones in the oriental fire-bellied toad, Bombina orientalis, is described. Data are based primarily on samples of ten or 11 laboratory-reared specimens of each of 11 Gosner developmental stages (36-46) representing middle through late metamorphosis. Ossification commences as early as stage 37 (hind limb with all five toes distinct), but the full complement of adult bones is not attained until stage 46 (metamorphosis complete). Number of bones present at inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
52
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(54 citation statements)
references
References 16 publications
2
52
0
Order By: Relevance
“…This is consistent with previous findings where, even under differential environmental conditions, sequences of chondrification and ossification are fairly stable (Mabee et al, 2000;Cloutier et al, 2010); the reported variation in relative order of events was low and often characterized by shifts of one or two positions of responsive elements within the sequences (Hanken and Hall, 1984;Alberch and Blanco, 1996;Mabee et al, 2000;Cloutier et al, 2010). However in these studies, onset of events was determined by direct observation of only a few specimens instead of being modeled as such potential bias might have been introduced in the relative order of events within sequences.…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with previous findings where, even under differential environmental conditions, sequences of chondrification and ossification are fairly stable (Mabee et al, 2000;Cloutier et al, 2010); the reported variation in relative order of events was low and often characterized by shifts of one or two positions of responsive elements within the sequences (Hanken and Hall, 1984;Alberch and Blanco, 1996;Mabee et al, 2000;Cloutier et al, 2010). However in these studies, onset of events was determined by direct observation of only a few specimens instead of being modeled as such potential bias might have been introduced in the relative order of events within sequences.…”
Section: Discussionsupporting
confidence: 93%
“…Although a number of authors have examined sequence change in evolution (e.g., Hanken and Hall, 1984;Irish, 1989;Hufford, 1995Hufford, , 1996Richardson, 1995;Cubbage and Mabee, 1996;Dunlap and Sanchiz, 1996;Mabee and Trendler, 1996;Velhagen, 1997;Larsson, 1998), a broadly applicable analytical or conceptual approach to sequence heterochrony has not yet emerged.…”
Section: Recapitulationmentioning
confidence: 98%
“…Few studies have reported significant intraspecific plasticity in the timing of events during vertebrate development, and, in most cases, these changes are associated with an environmental cue or manipulation. For example, with respect to the skeletal system there appears to be a small (but likely evolutionarily significant) amount of intraspecific variation in the sequence of skull bone development in some species of fish (Mabee et al, 2000) and perhaps significant variation in the timing of bone ossification in larval fire-bellied toads (Hanken and Hall, 1984). Muscle development is known to be plastic and responsive to a number of environmental variables in several species of fish (e.g.…”
Section: Different Developmental Trajectoriesmentioning
confidence: 99%